Effect of computer animation instruction on senior school students’ learning outcomes in atomic and nuclear physics, Kwara State, Nigeria - Shehu, Abdulrazaq; Akanbi, Abdulrasaq Oladimeji; Yahaya, Quadri; Yahaya, Wasiu Olayinka; Adeniyi, Gloria Ibidun; Abdulkadir, Abubakar Salman (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2024)
This study investigates the impact of computer animation instructional strategy on senior school students' performance and retention in atomic and nuclear physics in Kwara State, Nigeria. The researchers used a pre-test, and post-test design with a non-randomized, non-equivalent control group. The target population comprised all SS3 physics students in Kwara State. Two co-educational public senior secondary schools were selected from two out of the sixteen Local Government Areas in Kwara State, employing a sampling technique that involves multiple stages. Two intact classes, comprising 177 students were involved in the study. The instruments used for data collection were the Atomic and Nuclear Physics Performance Pre-Test (ANPPT I), Atomic and Nuclear Physics Performance Post-Test (ANPPT II), and Atomic and Nuclear Physics Retention Test (ANPRT). The instruments' reliability, carried out by experts, was 0.87. The research questions were answered using mean and standard deviation, and the null hypotheses were tested using the t-test and ANCOVA. The study's findings indicated a significant difference in mean scores between the experimental and control groups, which favoured the experimental group. Additionally, there was a significant difference in mean retention scores between the experimental and control groups, with the experimental group exhibiting higher scores. Notably, neither score level nor gender had a significant impact on either performance or retention. Based on the results, it was suggested that educational authorities at both the Federal and State Ministries of Education should organize workshops and seminars for teachers, focusing on utilizing computer animation as an instructional strategy to enhance students' performance in physics.